Penerapan Teknologi Tepat Guna Pada Pembuatan Jahe Instan Di SDN 4 Jepang - Mera Putri Pratitis; Dessy Erliani Mugita Sari; Dwi Susiloningrum; Ricka Islamiyati; Wildayanti Wildayanti (Lembaga Pengembangan Kinerja Dosen, 2023)
Appropriate technology has simple principles that aim to improve the socio-economic standard of living for the community by processing natural resources wisely and not damaging the surrounding environment. Natural resources in the surrounding environment are easy to find, especially Medicinal Plants. Medicinal Plants are widely found and consumed, one of which is ginger (Zingibers officinale rosc). Various groups, including children, can consume ginger. However, children's interest in consuming ginger or ginger ale is very low. The aim of this activity is to teach students how to make instant ginger powder so they can increase their interest in consuming ginger and other traditional medicinal plants. Activities were carried out using the service learning method for students at SDN 4 Jepang. Implementation of activities includes education, assistance, and training in making instant ginger powder. The implementation of activities is well done and smoothly. Students who participated in the activities were very enthusiastic and interested. All students participated in making instant powder starting from peeling ginger, grinding ginger, squeezing ginger juice, pressing ginger to mixing ginger into crystals/powder.